2018
DOI: 10.1242/dev.156257
|View full text |Cite
|
Sign up to set email alerts
|

A genetically encoded fluorescent probe for imaging of oxygenation gradients in living Drosophila

Abstract: Oxygen concentrations vary between tissues of multicellular organisms and change under certain physiological or pathological conditions. Multiple methods have been developed for measuring oxygenation of biological samples and However, most require complex equipment, are laborious and have significant limitations. Here we report that oxygen concentration determines the choice between two maturation pathways of DsRed FT (Timer). At high oxygen levels, this DsRed derivate matures predominantly into a red fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…While newly synthesized mitoTimer fluoresces green, the fluorescence shifts irreversibly to red over time due to dehydrogenization of the Tyr-67 residue (Verkhusha et al, 2004; Yarbrough et al, 2001). The change in fluorescence spectra and the means by which it occurs has made mitoTimer a useful tool to examine mitochondrial turnover and transport, as well as reporting cumulative redox and oxygenation history (Ferree et al, 2013; Hernandez et al, 2013; Laker et al, 2014; Stotland and Gottlieb, 2016; Laker et al, 2017; Wilson et al, 2019; Lidsky et al, 2018). We used mitoTimer to first examine changes in the state of mitochondria during neuromast maturation.…”
Section: Resultsmentioning
confidence: 99%
“…While newly synthesized mitoTimer fluoresces green, the fluorescence shifts irreversibly to red over time due to dehydrogenization of the Tyr-67 residue (Verkhusha et al, 2004; Yarbrough et al, 2001). The change in fluorescence spectra and the means by which it occurs has made mitoTimer a useful tool to examine mitochondrial turnover and transport, as well as reporting cumulative redox and oxygenation history (Ferree et al, 2013; Hernandez et al, 2013; Laker et al, 2014; Stotland and Gottlieb, 2016; Laker et al, 2017; Wilson et al, 2019; Lidsky et al, 2018). We used mitoTimer to first examine changes in the state of mitochondria during neuromast maturation.…”
Section: Resultsmentioning
confidence: 99%
“…Each maturation step requires an oxygen molecule that renders DsRed FT a natural oxygen sensor. In their work, Lidsky et al demonstrated that the blue-to-red conversion efficiency strongly depends on the medium oxygenation (9-21% O 2 concentrations were tested) [43]. Taking advantage of this observation, they developed the nlsTimer probe by fusing DsRed FT with a nuclear localization signal that enabled the confocal imaging of the oxygenation state of Drosophila melanogaster larvae cells during early development.…”
Section: Chromophore Maturation-based Reportersmentioning
confidence: 99%
“…The main drawbacks of nlsTimer include its slow maturation time (days) and irreversible character of the response. In the original study, the authors implemented a system consisting of hs-GAL4 and UASt-nlsTimer constructs that allows the capture of oxygenation memory maps after heat shock in poikilothermic animal models, which reflect the average oxygen concentrations during chromophore formation rather than rapid changes [43]. The implementation of degrons could increase turnover of the probe, paving the way for repetitive imaging experiments (possible approaches are discussed in the context of HIF system-based reporters).…”
Section: Chromophore Maturation-based Reportersmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of GFP‐like proteins with O 2 ‐independent fluorophores based on flavin mononucleotides has generated a FRET biosensor in E. coli (Potzkei et al , 2012). Furthermore, a two‐color DsRed protein has been developed, whose properties of O 2 ‐dependent maturation determined a quantitative shift in FRET emission from red to green that could be used to monitor hypoxia in Drosophila (Lidsky et al , 2018). Maturation‐type ratiometric biosensors may also be obtained using tandem fluorescent protein timers (tFT).…”
Section: In Vivo Biosensors For Plant Cellular Hypoxiamentioning
confidence: 99%